PENGEMBANGAN MEDIA CROSSWORD PUZZLE MATA PELAJARAN IPAS SDN 231 PALEMBANG - Herawati, Rahmi; Jujur Gunawan Manullang; Yusni Arni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The use of media in elementary schools today has become an innovative method to enhance student engagement in mastering learning materials. This study aims to determine the validity and practicality of the developed media in the form of a crossword puzzle for elementary school use. The type of research used is Research and Development (R&D) employing the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The product developed is a crossword puzzle media for the IPAS subject in Grade IV at SDN 231 Palembang. Data analysis techniques for product validity were obtained through validation by media experts, subject matter experts, and language experts. Meanwhile, the analysis of practicality was obtained from student response questionnaires. Based on the results of validations from media experts, subject matter experts, and language experts, the average score was 88%, categorized as